2016
DOI: 10.1016/j.jnucmat.2015.12.044
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesis and characterization of uranium carbide using high temperature neutron diffraction

Abstract: We investigated the formation of UCx from UO2+x and graphite in situ using neutron diffraction at high temperatures with particular focus on resolving the conflicting reports on the crystal structure of non-quenchable cubic UC2. The agents were UO2 nanopowder, which closely imitates nano grains observed in spent reactor fuels, and graphite powder. In situ neutron diffraction revealed the onset of the UO2 + 2C  UC + CO2 reaction at 1440˚C, with its completion at 1500˚C. Upon further heating, carbon diffuses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
(61 reference statements)
1
3
0
Order By: Relevance
“…Wen et al [35] found, however, that the oscillation is not spherical, as described by Bowman, but rather an oscillation approximately around the static location of the C-C dumbbells in the pyrite structure. Analysis of our diffraction data [34] confirm the structure reported by Bowman et al, (also determined by neutron diffraction).…”
Section: Modeling Relevance Of Neutron Diffraction Data 231 High Tesupporting
confidence: 91%
See 3 more Smart Citations
“…Wen et al [35] found, however, that the oscillation is not spherical, as described by Bowman, but rather an oscillation approximately around the static location of the C-C dumbbells in the pyrite structure. Analysis of our diffraction data [34] confirm the structure reported by Bowman et al, (also determined by neutron diffraction).…”
Section: Modeling Relevance Of Neutron Diffraction Data 231 High Tesupporting
confidence: 91%
“…Further increase of the sample temperature allowed us to follow the thermal expansion of the UC x phase. However, even during the dwell times at constant temperatures we observed changes in lattice parameters [34]. We attribute this to the continuation of the migration of carbon atoms into the uranium carbide.…”
Section: In Situ High Temperature Neutron Diffraction Uraniamentioning
confidence: 73%
See 2 more Smart Citations